PENDIDIKAN KELUARGA PERSPEKTIF BARAT DAN ISLAM (KAJIAN PSIKOLOGI KELUARGA MENURUT ZAKIAH DARADJAT) - Arroisi, Jarman; Perdana, Martin Putra (Universitas Muhammadiyah Ponorogo, 2021)
Zakiah Daradjat is present as a family consultant, psychologist and observer of Indonesian Islamic education. Many works are very influential, especially in the realm of psychology and education. With a background of extensive thinking and experience, Zakiah Daradjat is able to formulate psychiatric problems that are difficult to solve including marriage and family relationship problems. The existence of a gap in a family is not to be imagined, especially regarding children. Problems arise when the parents lack teach their children by religious education. Whereas religious education is not only teach religious knowledge and train children in performing worship. However religious education also should be establish personality of children in accordance with religious teachings. Using critical analyst methods supported by adequate literature, this paper will seek to uncover Zakiah Daradjat's version of the family model that is expected to be able to answer inequalities in terms of education and modern family relations.